Male Gaze In Charlotte Brontë’s Jane Eyre and Sutan Takdir Alisjahbana’s Layar Terkembang - Siswantia Sar; Nafisa Syahida Rahmadini (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2023)
This paper aims to discuss how the female body has been an object for male sexual pleasure in patriarchal culture. Female body is considered as the focus of the male gaze. This research uses a feminist theory by Laura Mulvey that focuses on sexual objectification of women. Data analysis was performed through qualitative descriptive techniques by interpreting the data found in Jane Eyre by Charlotte Brontë and Layar Terkembang by Sutan Takdir Alisjahbana. This paper aims to expose how smart, independent, and strong women still cannot break free from the male gaze. Women see themselves through the eyes of the men. Consciously and unconsciously, women do not only shape their physical appearance but also their ideology based on the male gaze Despite the fact that these novels were written at different times and places, Brontë and Alisjahbana raised the same theme about women empowerment through the main female characters. The result of this study shows that both authors have failed to fully create strong and independent female characters since both of the characters were still confined by the male gaze.